2007
DOI: 10.1016/j.jaci.2006.11.214
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Estrogens Induce Mast Cell Degranulation and Enhance IgE-mediated Release of Allergic Mediators

Abstract: BACKGROUND: Prevalence and morbidity of allergic diseases have increased over the last decades. Based on the recently recognized differences in asthma prevalence between the sexes, we have examined the effect of endogenous estrogens on a key element of the allergic response. Some lipophilic pollutants have estrogen-like activities and are termed environmental estrogens. These pollutants tend to degrade slowly in the environment and to bioaccumulate and bioconcentrate in the food chain; they also have long biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…Recently, it has been shown in 2 experimental studies [21,22] that estradiol and estrogen-like compounds stimulate (through a mast cell membrane estrogen receptor-a) the synthesis and release of allergic mediators. They also enhance IgE--dependent mast cell activation and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown in 2 experimental studies [21,22] that estradiol and estrogen-like compounds stimulate (through a mast cell membrane estrogen receptor-a) the synthesis and release of allergic mediators. They also enhance IgE--dependent mast cell activation and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study enrolling children from Brazil exposed to DDT showed that the immune response to diptheria vaccine was not impaired [37]. Prenatal DDE exposure increases also the rate of asthma in children (relative risk of 2.6) [38]; in vitro studies showed that DDT induces an increase in the rate of mast-cell degranulation therefore augmenting the risk of allergy [39,40]. In (NZB × NZW) F1 lupus prone mice, DDT exposure markedly increased the incidence of albuminuria, reduced uterine weight but had no measured effects on immunity or mortality [41].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…High dose studies have predominated in toxicology because scientists assume these studies can indicate the target of low dose exposure. However, some environmental toxicants display non-linear dose-response relationships, which means they cause different effects at different doses, and the impacts at low doses may not occur at high doses (Andrade et al, 2006;Narita et al, 2007;Wetherill et al, 2002;Wozniak et al, 2005). Recently, PBDEs have been reported to display apparent non-monotonic effects in experimental rats.…”
Section: Introductionmentioning
confidence: 99%